Molecular classification of hepatocellular carcinoma: potential therapeutic implications - Goossens, Nicolas; Sun, Xiaochen; Hoshida, Yujin (Hepatic oncology, 2015)
Genomic profiling of hepatocellular carcinoma (HCC) tumors has elucidated recurrent molecular aberrations common or specific to disease etiology, patient race or geographic regions, allowing the classification of HCC tumors into subclasses sharing similar molecular and clinical characteristics. Previously reported transcriptome-based molecular subclasses have highlighted several common themes. Aggressive tumors are characterized by TP53 inactivation mutations and activation of pro-oncogenic signaling pathways, and further subclassified according to expression of stemness markers. The stemness marker-negative aggressive tumors display preferential TGF-β activation. Another group of less aggressive tumors contains a subclass characterized by CTNNB1 mutations accompanied with overexpression of liver-specific WNT targets such as GLUL. Molecular therapies selectively targeting features of the HCC subclasses have suggested their utility in enriching potential responders in clinical trials and guiding therapeutic decision-making for HCC patients.